Static vs. dynamic liking in chewing gum: A new approach using a background task and a natural setting - Galmarini, Mara Virginia (2015)
Chewing gum is a particular product, consumed during long periods of time and usually while doing something else. Therefore, traditional hedonic tests might not provide sufficient information. The aim of the present work was to compare the liking scores resulting from asking consumers whether they liked the product only once (static liking, SL) to those obtained when asking repeatedly during consumption (dynamic liking, DL). For this purpose, three different mint chewing gums were evaluated by two groups of 50 consumers. In both cases, consumers evaluated the samples at home using an Internet application specifically designed for the experiment. In the SL, consumers were prompted to rate their liking only after 5 minutes of chewing. During this time, consumers were presented with a series of curious facts (?Did you know???) which they would read from the screen as a background task. For the DL, consumers were asked to rate the samples every 45 seconds during a period of 10 minutes while performing the same background task, having a maximum of 10 seconds to answer. Comparing the results obtained by both techniques at the same moment of consumption (5 min), ratings were found to be significantly higher with the SL for all samples. This could indicate that, when asked once, consumers gave their overall liking score and not their liking at precisely 5 minutes. Nonetheless, at that moment, the sample ranking was the same for both methods. Moreover, DL showed that when taking into account preference throughout consumption time, a significant product ranking inversion could be found, revealing that preference was time dependent and also that this change was different among products.